The China's Poverty Alleviation Strategies and Its Impacts - Min, Song (UNIMAS, 2026)
Eradicating poverty, cultivating a culture of improved livelihood, and attaining shared prosperity are the aspirations and expectations of people around the World. The Communist Party of China (CPC) and the Chinese government have always regarded poverty eradication as important in governing and rejuvenating the country. Under the leadership of the CPC, with President Xi Jinping as its leader, China has adopted innovative reforms and targeted poverty alleviation strategies. After more than eight years of tireless effort, China finally completed the difficult task of eradicating absolute poverty in 2021 and this achievement is significant. This research aims to study the concept and process of China’s poverty alleviation strategies, focusing on innovative theoretical advancement, the challenges and shortcomings within China’s poverty reduction approach. This research is firmly grounded in Marxist theory, using desktop analysis, historical and theoretical research methods, and comparative research methods to explore the theory and practice of China’s poverty alleviation. Using systematic scientific research approaches, the research compiles a comprehensive account of China’s poverty alleviation journey and the multi-dimensional measures undertaken by the CPC to lead poverty alleviation practice across society. The main findings indicated that China’s success story began with the rural poor, who were the backbone of China’s economy. This was followed by targeted poverty measures that focuses on adaptation and innovative approaches into various key sectors (case study of photovoltaic poverty alleviation, health-based interventions and employment-based poverty strategy). Findings indicated that adjustments of policies to socioeconomic changes, and shifting poverty distributions are key to China’s poverty eradication approaches. In short, this study fills the gap in the body of knowledge on China’s efforts on poverty alleviation strategies. It also provides learning model for global poverty eradication strategies. However, the findings are based solely on China’s examples, and therefore, has limited references to international poverty eradication experiences.